Impact of linear infrastructure and landscape characteristics on wildlife roadkill in the Nelliyampathy Hills, Western Ghats, India - S. Sushanth; G. Praphul; S. R. Ganesh; Sanjay Molur; Honnavalli N. Kumara; Mewa Singh (Scientific Reports)
Abstract The expansion of linear infrastructures, such as roads, which are integral to human society, poses a serious threat to wildlife, leading to road accidents, which have become major causes of terrestrial and avian wildlife mortality worldwide. This study, conducted from June 2023 to May 2024 in the Nelliyampathy Hills, Western Ghats, Kerala, India aimed to assess terrestrial and avian vertebrate roadkill, and the environmental parameters influencing it. In 22 roadkill surveys, 330 roadkills were recorded, representing 72 species, that included 228 individuals of reptiles (43 species) (66.09%), 70 amphibian individuals (11 species) (20.29%), 23 mammal individuals (10 species) (9.57%), and 9 bird individuals (8 species) (4.06%). The annual roadkill estimate was 5,490 along a 50 km transect, with an overall roadkill rate of 0.3 roadkills/km/year. Environmental factors such as plantations, road pavement, water sources, terrain, and undergrowth were found to significantly influence roadkill occurrences. However, there was negligible spatial and seasonal variation in roadkill hotspots. This communication presents advisory measures to reduce wildlife mortality from vehicle collisions to support ecosystem health and minimize such wildlife mortality.